Diagnosis and treatment of Kaposi's sarcoma: European consensus-based interdisciplinary guideline (EDF/EADO/EORTC). (June 2019) - Lebbe, Celeste; Garbe, Claus; Stratigos, Alexander J.; Harwood, Catherine; Peris, Ketty; Marmol, Veronique del; Malvehy, Josep; Zalaudek, Iris; Hoeller, Christoph; Dummer, Reinhard; Forsea, Ana Maria; Kandolf-Sekulovic, Lidija; et al.
Abstract: Kaposi's sarcoma (KS) is a multifocal neoplasm of lymphatic endothelium-derived cells infected with human herpesvirus 8. Four clinical subtypes are distinguished: the classic, the endemic, the epidemic subtype in HIV positive patients and the iatrogenic subtype. The diagnosis is primarily based on clinical features and confirmation by histology with immunohistochemistry. Cutaneous distribution and severity, mucosal, nodal and visceral involvement depend on the type of KS with in general indolent behaviour and chronic evolution in the classic subtype and the more severe forms in iatrogenic or epidemic subtypes. Management should aim at achieving disease control. For localised lesions, several local therapies have been developed without randomised trial comparisons. Radiotherapy, intralesional chemotherapies and electrochemotherapy have high response rates. Topical treatments—imiquimod or topical 9-cis-retinoid acid—can also be used. Systemic treatments are reserved for locally aggressive extensive and disseminated KS: the recommended first-line agents are pegylated liposomal doxorubicin (PLD) and paclitaxel. In CKS, PLD or low-dose interferon-alfa are the recommended first-line agents in younger patients. In AIDS-related KS, combination antiretroviral therapy is the first treatment option; specific systemic treatment is needed only in case of extensive disease and in the prevention and treatment of immune reconstitution inflammatory syndrome. In post-transplant KS, tapering down immunosuppressive therapy and switching to mammalian target of rapamycin (m-TOR) inhibitors are used. Follow-up schedules for patients with KS disease depend on aggressiveness of the disease. Highlights: Kaposi's sarcoma (KS) is a human herpesvirus-8–associated multicentric lymph endothelial proliferation. KS severity depends on the level of concomitant immunosuppression which ought to be minimised if possible. Workup depends on the setting, HIV infection or transplantation and patient's symptoms. Local and systemic specific agents can be highly effective but are unable to cure the disease.